Bunt Michała przeciw carowi Piotrowi (?930). - Leszka, Mirosław J. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
The article refers to the repeatedly discussed subject of the rebellion staged by Michael, the son of Simeon I of Bulgaria, against Peter his (?)step-brother. The author of the study has re-analysed sources on the uprising for the motives behind the conspiracy and its scope. The conspiracy has been concluded to have primarily been an aspect of the struggle for power amongst the successors of Simeon.